Proteomic analysis of salivary glands of female Anopheles barbirostris species A2 (Diptera: Culicidae) by two-dimensional gel electrophoresis and mass spectrometry - Jariyapan N. (2014)
Salivary gland proteins of adult female Anopheles barbirostris species A2, a potential vector of Plasmodium vivax in Thailand, were analyzed using a proteomic approach (two-dimensional gel electrophoresis followed by nanoLCMS). Two-dimensional gel electrophoresis revealed approximately 75 well-resolved spots on the reference gel. Most of the protein spots displayed relative molecular masses from 14 to 85 kDa and isoelectric points ranging from 3.9 to 10. The proteome profiles of A. barbirostris species A2 female salivary glands were affected by aging. The typical electrophoretic pattern of the female salivary glands was reached in 48 h post emergence, suggesting the maturation of salivary glands and saliva contents for blood feeding. Proteins involved in blood feeding, i.e., putative 5' nucleotidase/ apyrase, anti-platelet protein, long form D7 salivary protein, D7-related 1 protein, and gSG6 salivary protein, start to accumulate from emergence and gradually increase becoming predominant within 48 h. There are different salivary components expressed within each region of the female glands. The blood-feeding proteins were detected in the distal-lateral lobes and/or medial lobes. Proteins detected and/or identified by this approach could be tested in strategies developed to control pathogen and disease transmission. Moreover, the information of a 2D map of the female salivary gland could be used for comparison with other related species in the A. barbirostris complex to distinguish species members in the complex. © Springer-Verlag 2012.